Effect of Binaural Stimulation on Attention and EEG - CRESPO, Adela; RECUERO, Manuel; GALVEZ, Gerardo; BEGONA, Adrian (Archives of Acoustics, 2013)
When two pure tones of slightly different frequency are presented separately to each ear, the listenerperceives a third single tone with amplitude variations at a frequency that equals the difference betweenthe two tones; this perceptual illusion is known as the binaural auditory beat (BB). There are anecdotalreports that suggest that the binaural beat can entrain EEG activity and may affect the arousal levels,although few studies have been published.There is a need for double-blind, well-designed studies in order to establish a solid foundation forthese sounds, as most of the documented benefits come from self-reported cases that could be affected byplacebo effect. As BBs are a cheap technology (it even exists a free open source programmable binaural-beat generator on the Internet named Gnaural), any achievement in this area could be of public interest.The aim in our research was to explore the potential of BBs in a particular field: tasks that requirefocus and concentration. In order to detect changes in the brain waves that could relate to any particularimprovement, EEG recordings of a small sample of individuals were also obtained.In this study we compare the effect of different binaural stimulation in 7 EEG frequency ranges. 78participants were exposed to 20-min binaural beat stimulation. The effects were obtained both quali-tative with cognitive test and quantitative with EEG analysis. Results suggest no significant statisticalimprovement in 20-min stimulation.